Chondroitin sulphate at the endothelial lumen of pig aorta: Assay by radiolabelling and by X-ray microanalysis. Issue 3 (March 1987) - Hale, G.; Streeter, H. B.; Hann, A. C.; Gacesa, P.; Wusteman, F. S.
Abstract : Trypsin-releasable glycosaminoglycans from the luminal surface of intact pig aorta were measured following metabolic labelling with 35 S]sulphate. Chondroitin sulphate was found to be present at a surface density equal to that already established for heparan sulphate (5×10 11 chains per cm 2 ). This result was confirmed by X-ray microanalysis of the luminal sulphur content before and after treatment with specific glycosaminoglycan-degrading enzymes. This result implies that approximately half of the luminal surface is occupied by sulphated glycosaminoglycans.